The capability of heterogeneous γδ T cells in cancer treatment - Yan, Wenyi; Dunmall, Louisa S. Chard; Lemoine, Nicholas R.; Wang, Yaohe; Wang, Yafeng; Wang, Pengju (Frontiers in Immunology, 2023)
γδ T cells, a specialized subset of T lymphocytes, have garnered significant attention within the realm of cancer immunotherapy. Operating at the nexus between adaptive and innate immunological paradigms, these cells showcase a profound tumor discernment repertoire, hinting at novel immunotherapeutic strategies.γδ T cells are a unique subset of T lymphocytes that have shown promise in the field of cancer immunotherapy. These cells, which serve as a bridge between the adaptive and innate immune systems, possess an extensive range of tumor sensing abilities and offer innovative applications in immunotherapy. They can directly recognize and kill tumor cells independently of HLA-antigen presentation. In addition, γδ T cells can present tumor antigens to αβ T cells to enhance their anti-tumoral activity. Significantly, these cells possess the capability to directly identify and eliminate tumor cells without reliance on HLA-antigen presentation. Furthermore, γδ T cells have the faculty to present tumor antigens to αβ T cells, amplifying their antitumoral efficacy.Within the diverse and heterogeneous subpopulations of γδ T cells, distinct immune functionalities emerge, manifesting either anti-tumor or pro-tumor roles within the tumor microenvironment. γδ T cells with multiple heterogeneous subpopulations generate unique immune functions that are either anti-tumor or pro-tumor in the tumor microenvironment. Understanding and adapting to utilize heterogeneous subpopulations of γδ T cells is key to γδ T cell-associated tumor immunotherapy. Intensive study of γδ T cell plasticity may hold great promise for cancer